Falling through the social safety net? Analysing non-take-up of minimum income benefit and monetary social assistance in Austria - Michael Fuchs; Katarina Hollan; Katrin Gasior; Tamara Premrov; Anette Scoppetta (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Non-take-up of means tested benefits is a wide spread phenomenon in European welfare states. The paper assesses whether the reform that replaced the monetary social assistance benefit by the minimum income benefit in Austria has succeeded in increasing take up rates. We use EU-SILC register data together with the tax-benefit microsimulation model EUROMOD/SORESI. The results show that the reform led to a significant decrease of non-take-up from 53% to 30% in terms of the number of households and from 51% to 30% in terms of expenditure. Estimates of a two-stage Heckman selection model show that pecuniary determinants (higher degree of need), lower applications costs (unemployment, low education, renting one's home) and lower psychological barriers (size of municipality and lone-parenthood) are predictors of taking up the benefit.
Keywords: D61; H31; I38; 330; Non-take-up; Means-tested benefits; Microsimulation; Social Policy